Synthesis and functional properties of TiO₂–Pt/Pd electrocatalysts - Ковтунов, Дмитро; Черних, Сергій; Книш, Валентин; Шмичкова, Олеся; Лук'яненко, Тетяна; Веліченко, Олександр (Київський національний університет імені Тараса Шевченка, 2025)
Background. This study is focused on the development and comprehensive characterization of novel composite electrocatalytic materials based on porous titanium dioxide modified with Pt and Pd. The primary objective was to create highly efficient and stable systems for electrocatalytic applications, particularly for reactions involving high anodic potentials, such as the oxygen evolution reaction. Methods. The porous TiO2 matrix was synthesized using a two-step anodization process of titanium foil in ethylene glycol-based electrolytes containing ammonium fluoride / phosphoric acid, followed by electrochemical reduction in a perchloric acid solution. This method allowed for precise control over the morphology and specific surface area of the resulting oxide layer. Modification with noble metals was achieved through galvanic deposition of Pt and/or Pd from appropriate plating baths, with subsequent thermal treatment at 500 °C in an air atmosphere. This crucial annealing step facilitated the formation of the final composite structure by promoting surface layer oxidation and the encapsulation of metal particles within the titanium oxide matrix. The morphology, elemental composition, and phase structure of the synthesized composites were investigated using scanning electron microscopy, energy-dispersive X-ray spectroscopy, and powder X-ray diffraction. Results. The analyses confirmed the formation of a developed porous microstructure with a uniform distribution of Pt and Pd nanoclusters. The phase composition was predominantly anatase, with the presence of metallic Pt and Pd, as well as palladium oxide. The electrochemical properties were evaluated through quasi-stationary voltammetry and electrochemical impedance spectroscopy in a 1 M HClO4 solution. The materials exhibited semiconductor behavior of the n-type with a high charge carrier concentration, as determined by Mott-Schottky analysis. The TiO2-Pt composite demonstrated the highest activity in the OER, characterized by a Tafel slope of 122 mV/dec. The bimetallic system, while showing a higher Tafel slope (172 mV/dec) indicative of a more complex reaction mechanism influenced by the semiconductor properties of the substrate, displayed exceptional operational stability. It retained its catalytic activity and structural integrity for over 215 hours under severe testing conditions (0.5 A, 1 M HClO4), significantly outperforming the unstable Pd-only modified electrode. Conclusions. The research establishes a correlation between the synthesis conditions, the structural characteristics of the composites, and their functional electrocatalytic properties. The developed composites show significant promise for use as durable anode materials in various electrochemical processes, including oxygen evolution, and serve as a foundational template for further development of advanced (photo)electrocatalysts. The proposed synthesis strategy offers a viable route for creating efficient electrocatalysts with reduced noble metal content.

Вступ. У роботі представлено результати створення та комплексної характеристики нових електрокаталітичних композитів на основі пористого TiO2, модифікованого Pt і Pd. Мета дослідження – розробка ефективних і стабільних систем для процесів, що перебігають за високих анодних потенціалів, зокрема реакції виділення кисню. Методи. Матрицю TiO₂ отримували двоетапним анодуванням титанової фольги в електролітах на основі етиленгліколю з NH4F і H3PO4, а потім відновлювали в розчині HClO4. Такий підхід забезпечив контроль над морфологією та питомою поверхнею оксидного шару. Модифікацію Pt і Pd здійснювали гальванічним осадженням із подальшим відпалом за 500 °C на повітрі, що сприяло окисненню поверхні та інкапсуляції металевих частинок у матрицю TiO2. Морфологію та фазовий склад вивчали методами скануючої мікроскопії, мікроаналізу та рентгенівської дифракції. Результати. Встановлено наявність розвиненої пористої структури з рівномірним розподілом нанокластерів Pt і Pd. Основна фаза – анатаз; також виявлено металічні Pt, Pd і PdO. Електрохімічні дослідження (вольтамперометрія, імпедансна спектроскопія) у 1 M HClO4 показали n-тип провідності з високою концентрацією носіїв заряду (аналіз Мотта–Шотткі). Композит TiO2–Pt продемонстрував найвищу активність у реакції виділення кисню (нахил Тафеля 122 мВ/дек). Біметалічна система мала більший нахил (172 мВ/дек), що свідчить про складніший механізм, однак відзначалася винятковою стабільністю: понад 215 годин без втрати активності за 0,5 А в 1 M HClO4. Для порівняння, електрод, модифікований лише Pd, виявився нестійким. Висновки. Виявлено зв’язок між умовами синтезу, структурними характеристиками та електрокаталітичними властивостями матеріалів. Розроблені композити мають значний потенціал як довговічні аноди для електрохімічних процесів та можуть стати основою для створення нових (фото)електрокаталізаторів зі зниженим вмістом благородних металів.
Синтез та функціональні властивості TiO₂–Pt/Pd-систем для електрокаталізу
Keywords: субоксид титану; інкапсуляція; благородні метали; виділення кисню; напівпровідникові властивості; titanium suboxide; encapsulation; noble metals; oxygen evolution reaction; semiconductor properties